2009
DOI: 10.1017/s1368980008003789
|View full text |Cite
|
Sign up to set email alerts
|

The impact of rapid economic growth and globalization on zinc nutrition in South Korea

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…An Asian study showed decreased serum zinc level in AD patients and they suggested that the empirical avoidance of seafood and meat in Hong Kong may be the possible cause (26). In Korean normal population, mean zinc intake has increased during the 1990s with a marked decrease of cereal consumption and an increase of meat and fish (27). The daily mean intake of zinc was more than that of the Korean Dietary Reference Intake (KDRI) and zinc absorption and balance were favourable in children (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…An Asian study showed decreased serum zinc level in AD patients and they suggested that the empirical avoidance of seafood and meat in Hong Kong may be the possible cause (26). In Korean normal population, mean zinc intake has increased during the 1990s with a marked decrease of cereal consumption and an increase of meat and fish (27). The daily mean intake of zinc was more than that of the Korean Dietary Reference Intake (KDRI) and zinc absorption and balance were favourable in children (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…5 However, in cases where highly-valued food (which people can afford with rising incomes) incidentally also contains higher levels of micronutrients, fighting poverty can automatically help reducing VMDs. For instance in one recent study Kwun et al (2009) found that Zn nutrition in South Korea improved markedly in the period of rapid economic growth between 1969 and 1998: lower Zn intakes due to decreased cereal consumption were counterbalanced by marked increases in the consumption of meat and fish as well as by improved Zn bioavailability due to reduced phytate consumption.…”
Section: Causes and Determinants Of Malnutritionmentioning
confidence: 99%
“…For instance (to refer to the most advanced biofortified GM crop), when Golden Rice was developed, the complexity resulting from fragmented intellectual property ownership was considered to represent a potential constraint for its commercial development (Delmer et al 2003;Kryder et al 2000). However, as one of its developers highlights, compared to the hurdles raised by the regulatory requirements for GMOs that Golden Rice has to comply with, the issue of sorting out the intellectual property rights (IPR) was only a minor one (Potrykus 2009).…”
Section: Current Developments and Constraintsmentioning
confidence: 99%
“…The likelihood of mild-to-moderate Zn deficiency ( 33 ) and lower plasma levels of Zn ( 34 ) is higher in pregnant women than in non-pregnant women. Despite a recent increasing trend of animal food consumption and a subsequent improvement in overall Zn bioavailability ( 35 ) , approximately 54 % of the Korean population has an inadequate Zn intake due to the traditionally high intake of white rice and vegetables ( 14 ) . The situation could be more critical for pregnant women, because the nutritional requirement for Zn is increased during pregnancy to meet the demands of fetal growth and the maintenance of maternal health.…”
Section: Discussionmentioning
confidence: 99%